PERBANDINGAN TINDAK PIDANA KORUPSI MENURUT UNDANG-UNDANG NO. 31 TAHUN 1999 Jo UNDANG-UNDANG No. 20 TAHUN 2001 TERHADAP RANCANGAN UNDANG-UNDANG KUHP TENTANG TINDAK PIDANA KORUPSI - Phio Tuah Reysario Sinaga; Mahmud Mulyadi; Muhammad Ekaputra; Jelly Leviza (Universitas Sumatera Utara, 2017)
ABSTRACT Corruption is always seen as a contagious disease and can proliferate in a particular network, does not stop at a single network, but rather to move from one network to another until completely destroyed tissue. Corruption is a crime which is seen as a high level of crime, not only because this crime is done through technical and systematic effort but the implications arising from this crime and undermine the entire system perarel affected by the corruption virus. Corrupt practices are often interpreted as positive, when this behavior becomes an effective tool to penetrate the public administration, and political channels were very closed. Corruption is also an effective tool to ease the tension between the bureaucrat and politically, because both are involved together in achieving compliance with their own personal interests. Whatever the reason, corruption tends to create economic inefficiencies and waste sector as it has a direct impact on the allocation of funds, production, and consumption funds. Corruption direct or will not affect the level of quality of goods and services Keywords: corruption, crime, extraordinary crime